Peculiarities of hydrodynamics of pumps for the extraction of high-viscosity oil - Pavlov, Danil Andreyevich; Peshcherenko, Sergey Nikolayevich (Computational Continuum Mechanics, 2019)
Special features of the offshore fields currently under development are the high production rate of wells ( 104bpd) and the high viscosity of the produced water-oil emulsion 102-103сP, depending on the water cut. There are no special pumps designed for these conditions, so the production is carried out by the traditional centrifugal pumps suitable for the low-viscosity applications. For the selection purpose their testing on benches is performed according to the methods adopted in the oil industry at a frequency of up to 58 Hz (3500 rpm). The only difference is that instead of the traditional low-viscosity working fluid (water) high-viscosity Newtonian fluids (such as glycerin and oil) are used. Such tests only approximately correspond to well conditions; the following factors are not taken into account: the change in the properties of the liquid along the pump, the increase in the energy efficiency of pumps at increased shaft speeds, and, finally, the non-Newtonian rheology of the extracted emulsions. In our bench tests the shaft speed and the number of pump stages varied. The tests were carried out both on high-viscosity Newtonian fluid and water-oil emulsion. It was shown that the viscosity of the Newtonian fluid, due to its heating along the pump decreased by 20-30%. Moreover, the heating is not only due to internal friction, but also due to the compression of the liquid. A method of measuring of the effective viscosity of emulsions (which depends not only on the properties of the emulsion, but also the nature of its flow) based on the pump testing results has been proposed. It is shown that when the pump supply is changed the effective viscosity changes by approximately a factor of 3 times. The important phenomenon of increase of the efficiency of the pumps by 10 % during growing the frequency of rotation of the shaft from a traditional 50 Hz to 100 Hz was established. This effect occurs on both Newtonian fluids and emulsions.